Ferroptosis: a dual-edged sword in tumour growth - Zhao, Xiangye; Li, Xiaoning; Xu, Yinghui (Frontiers in Pharmacology, 2024)
Ferroptosis, a recently identified form of non-apoptotic cell death, is distinguished by its dependence on iron-triggered lipid peroxidation and accumulation of iron. It has been linked to various disorders, including the development of tumours. Interestingly, ferroptosis appears to exhibit a dual role in the context of tumour growth. This article provides a thorough exploration of the inherent ambivalence within ferroptosis, encompassing both its facilitation and inhibition of tumorous proliferation. It examines potential therapeutic targets associated with ferroptosis, the susceptibility of cancerous cells to ferroptosis, strategies to enhance the efficacy of existing cancer treatments, the interaction between ferroptosis and the immune response to tumours, and the fundamental mechanisms governing ferroptosis-induced tumour progression. A comprehensive understanding of how ferroptosis contributes to tumour biology and the strategic management of its dual nature are crucial for maximizing its therapeutic potential.